Effect produced on ground reaction forces by a prefabricated, weight-bearing and non-weight-bearing foot orthosis in the treatment of pronated foot: Pilot study. - Gijón-Noguerón, Gabriel; Palomo-Toucedo, Inmaculada C.; Gil-Tinoco, Alejandro; Ortega-Ávila, Ana Belén; Munuera-Martínez, Pedro (Lippincott, 2018)
Background: The aim of this study is to explore the changes in ground reaction force (GRF) produced by custom-made weightbearing and nonweight-bearing foot orthoses and by a prefabricated foot orthosis, in the control of the pronated foot. Methods:Thirty-nine participants were recruited. All were in good health, aged 18 to 25 years, and presented pronated foot. Three different types of foot orthosis were studied: prefabricated, weight-bearing, and nonweight-bearing. Results: No significant differences were observed in the phases of the gait cycle between the prefabricated, the weight-bearing, and the nonweight-bearing foot orthoses. Conclusions: Neither prefabricated insoles nor custom-made orthoses (weight-bearing or nonweight-bearing) modified GRF. Abbreviations: ANOVA = analysis of variance, BW = body weight, CEUMA = Ethic Committee of the University of Málaga, FPI = foot posture index, GRF = ground reaction forces, SD = standard deviation, STJ = subtalar joint.
Keywords: Pies - Anomalías y malformaciones; Ortopedia; Foot orthosis; Gait analysis; Ground reaction force; Pronated foot